CLOVES Syndrome: A Review of Clinical, Genetic, and Therapeutic Aspects - Podolec, Julianna; Ciraolo, Silvia; Wojda, Joanna; Sobiński, Adam; Kościuszko, Zuzanna; Kurza, Katarzyna; Agnieszka Kulczycka-Rowicka; Czerwonka, Matylda; Lesiczka-Fedoryj, Katarzyna; Walczak, Anna (Quality in Sport, 2025)
Purpose of Research: The research aims to provide an in-depth understanding of CLOVES syndrome, detailing its clinical features, epidemiology, etiology, and diagnostic criteria. It focuses on the role of PIK3CA gene mutations, challenges in diagnosis, and treatment options, including PI3K/AKT/mTOR pathway inhibitors. Research Materials and Methods: This article is based on a review of the current literature and clinical reports from various sources. The methodology includes a collection and synthesis of clinical data, imaging findings, and genetic analyses from published case studies and medical literature. The primary materials used in the research include: clinical case reports and studies, imaging studies, genetic analysis, therapeutic interventions, epidemiological data, literature review and data analysis. Basic Results: CLOVES syndrome affects fewer than 200 individuals worldwide, with symptoms appearing at birth or early childhood. It can lead to serious complications such as nerve compression, deep vein thrombosis, and pulmonary embolism. Diagnosis involves genetic testing and imaging, and sirolimus shows potential in managing symptoms. Conclusions: CLOVES syndrome is a rare, non-hereditary overgrowth disorder caused by a PIK3CA gene mutation. Early diagnosis and a multidisciplinary approach are vital for managing this complex condition and improving patient outcomes.